Generation and Characterization of a Soybean Line with a Vernonia galamensis Diacylglycerol Acyltransferase-1 Gene and a myo-Inositol 1-Phosphate Synthase Knockout Mutation - AL-Amery, Maythem; Fowler, Ashley; Unrine, Jason M.; Armstrong, Paul; Maghirang, Elizabeth; Su, Kai; de Melo, Julia [UNESP]; Yuan, Feng-Jie; Shu, Qing-Yao; Hildebrand, David (Wiley, 2020)
Soybean (Glycine max) meal is an important protein source. Soybean meal with lower phytate and oligosaccharides improves meal quality. A single recessive mutation in soybean myo-inositol 1-phosphate synthase (Gm-lpa-TW75-1) confers a seed phenotype with low phytate and increased inorganic phosphate. The mutant was crossed with high oil lines expressing a diacylglycerol acyltransferase1 (DGAT) gene from Vernonia galamensis (VgD). Gm-lpa-TW75-1 X VgD, designated GV, has 21%, and 22% oil and 41% and 43% protein from field and greenhouse seed production, respectively. No significant differences were found in mineral concentrations except for Fe which was 229 μg/g dry mass for GV followed by 174.3 for VgD and 162 for Gm-lpa-TW75-1. Phosphate (Pi) is higher in Gm-lpa-TW75-1 as expected at 5 mg/g, followed by GV at 1.6 mg/g whereas Jack, VgD, and Taiwan75 have about 0.3 mg/g. The Gm-lpa-TW75-1 line has the lowest phytate concentration at 1.4 mg/g followed by GV with 1.8 mg/g compared to Taiwan75, VgD, and Jack with 2.5 mg/g. This work describes a high oil and protein soybean line, GV, with increased Pi and lower phytate which will increase the nutritional value for human and animal feed.
Keywords: Glycine max; High oil; High phosphate; High protein; Low phytate